Isolation and characterization of plasmids carrying a partially defective Escherichia coli replication origin. - Stuitje, A R (1983)
The replication origin (oriC) of the Escherichia coli chromosome has been cloned and the region essential for chromosomal replication has been delimited to 245 base pairs. In previous studies the ability of recombinants between oriC and ColE1-type vectors, to transform E. coli polA- strains was used to determine which nucleotides in oriC are essential for replication. In this paper we have used a different approach by isolating partial defective replication mutants of a minichromosome (pCM959) that contains oriC as the single replication origin. Our results demonstrate that many mutations are allowed within oriC that do not affect oriC function as measured by the ability to transform E. coli polA- strains. In the minimal oriC region we detected 8 mutations at positions that are conserved in the sequence of six bacterial origins. The implications of these results on previous work will be discussed. Our data also demonstrate that a mutation producing an oriC- phenotype may be suppressed by secondary mutations. An E. coli strain was found that facilitates the isolation of partially defective minichromosomes. The results with this strain indicate a specific function of the sequence surrounding the base pair at position 138.